Meningkatkan Jiwa Wirausaha Dengan Mengikuti Stand Bazar Kampus Sebagai Ajang Kreativitas Mahasiswa - Febrian, Rafico Rifki; Lidyawati, Citra Oktavina Eka; Muthoharoh, Siti Lulun; Mardikanigsih, Rahayu; Darmawan, Didit; Hariani, Mila; Putra, Arif Rachman; Arifin, Samsul (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
This community service aims to explore the role of campus bazaar stands in improving students' entrepreneurial spirit. Using the PAR method, a community service approach based on facts that occur in the field. This community service involves students of Sunan Giri University Surabaya who have participated in campus bazaar activities, students involved in the bazaar form useful networks and do good entrepreneurship among fellow participants. The results of the community service show that participation in campus bazaar stands not only hones technical business skills such as financial management and marketing strategies, but also develops soft skills such as communication, negotiation, and leadership. In addition, campus bazaar stands function as a platform for innovation and networking, which are important for future business success. This community service concludes that campus bazaar stands are an effective means of developing students' entrepreneurial spirit, supporting innovation, and facilitating practical learning in the context of entrepreneurship.